Women in charge: Do gender diversity and the participation of female heirs affect the performance of listed companies? (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This research verified the influence of gender diversity on the performance of listed companies in Brazil. Additionally, it was analyzed whether the existence of family ties between directors and executives and their colleagues affected the firms’ performance. Data from 2010 to 2017 were used, analyzed with the method of generalized moments. Results showed that less than 8% of seats on boards of directors and executive positions were held by women. It was confirmed that greater female participation in boards of directors and in executive positions leads to an increase in the performance of firms. However, the effect of the participation of directors and executives who had family ties with their colleagues was negative, opening space for discussion.